2018
DOI: 10.1002/asi.24110
|View full text |Cite
|
Sign up to set email alerts
|

Information behaviors in disadvantaged and dependent circumstances and the role of information intermediaries

Abstract: This article provides the first empirical study focused exclusively on the information intermediary role in disadvantaged (socioeconomic) and dependent (support) circumstances. We report findings from interviews and focus groups with 49 UK state and voluntary sector professionals providing support to young (<21) mothers from areas of multiple deprivations. We evidence an important information intermediary role with three key contributions to information behaviors in disadvantaged and dependent circumstances. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 32 publications
(52 reference statements)
7
54
0
Order By: Relevance
“…There is a need for more prescriptive guidance including methods to assist with elicitation and specification of information need in the problematic context. We also know from our participants and previous work (Buchanan et al, 2018a), that many young mothers have difficulties understanding information due to learning difficulties, and issues of cognitive load. Such issues point to the need for incremental and iterative learning cycles, and personalised information.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…There is a need for more prescriptive guidance including methods to assist with elicitation and specification of information need in the problematic context. We also know from our participants and previous work (Buchanan et al, 2018a), that many young mothers have difficulties understanding information due to learning difficulties, and issues of cognitive load. Such issues point to the need for incremental and iterative learning cycles, and personalised information.…”
Section: Discussionmentioning
confidence: 89%
“…Two recent information behaviour studies amongst at-risk populations (Buchanan and Tuckerman, 2016;Buchanan et al, 2018a) have contributed to our understanding of IL in the everyday context, and provided direction for this current work. Buchanan and Tuckerman (2016) in a study of adolescent information behaviours in disadvantaged and disengaged circumstances, worked with UK young people aged 16-19 not in education, employment or training (NEET), and their support workers.…”
Section: Introductionmentioning
confidence: 94%
“…There is evidence of the interplay of Wilson's (1997) stress and coping mechanisms known to influence initial action (or not) on needs, and in relation, an important support role provided by health professionals, evidenced in participant comments such as, "I was really struggling at one point and I got [family nurse] and other welfare officers to… help me.". Buchanan et al (2019) have previously identified such professionals as providing an important intermediary role, assisting young mothers with recognising and addressing needs. This study now evidences this important role from the mothers' perspectives.…”
Section: Rq1 What Are the Everyday Information Needs Of Disadvantagedmentioning
confidence: 99%
“…The second quadrant is digital systems (e.g., how digital products are accessed), which includes human capital that impacts a user's capacity to interact with the system (Buchanan et al, 2016). The digital systems quadrant is defined as a distributed, adaptive, open socio-technical system with properties of self-organization, scalability and sustainability inspired from natural systems.…”
Section: User-centred Model: a Systems Viewmentioning
confidence: 99%